2001
DOI: 10.1017/s0028688501000108
|View full text |Cite
|
Sign up to set email alerts
|

The Cultural Milieu of Ancient Sepphoris

Abstract: Recent New Testament scholarship has rightly emphasized the significance of urban features at Sepphoris for gospels and Historical Jesus research. However, some of these studies have greatly exaggerated the quantity of evidence for Greco-Roman influence in the first-century city. Most of the architectural features associated with the Greco-Roman city are missing, evidence for use of Greek is minimal, and signs of pagans are rare. In light of this, questions about the influence of Galilee's Hellenistic milieu o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Public architecture is of course more instructive as to the ruler's cultural orientation than that of the ordinary people (Reed 2000:43). And generally, archaeological investigations have revealed that Sepphoris was overwhelmingly inhabited by "Jews" (Chancey 2001;2002:79-80). The four "religious", or rather, ethnic indicators that have been found all over Galilee (lack of pork in the bone profile, miqva'ot, stone vessels, and burial in kochim or loculi tombs with ossuaries) are also present in the excavations conducted in Sepphoris.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Public architecture is of course more instructive as to the ruler's cultural orientation than that of the ordinary people (Reed 2000:43). And generally, archaeological investigations have revealed that Sepphoris was overwhelmingly inhabited by "Jews" (Chancey 2001;2002:79-80). The four "religious", or rather, ethnic indicators that have been found all over Galilee (lack of pork in the bone profile, miqva'ot, stone vessels, and burial in kochim or loculi tombs with ossuaries) are also present in the excavations conducted in Sepphoris.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Cf. Reed 2000: 79-82, 94-95; Chancey 2001: 127-45; 1992: 84-91.…”
unclassified